Fracture Resistance of Endodontically Treated Teeth Restored with Endocrown, Full Veneer Crowns and Onlays Made of Lithium Disilicate Glass Ceramic: An In-vitro Study - Shefali Singla, Lalit Kumar, Sunint Singh, Naveen Yadav, Dhananjay Arora, Charnpreet Singh (RUHS Journal of Health Sciences)
Introduction: The present in-vitro study was performed to compare the fracture resistance of endodontically treated mandibular molars restored with lithium disilicate ceramic full veneer crowns, onlays, and endocrowns. Methodology: The study included forty human mandibular first molars divided into four groups ie group C, FVC, O and E. Group C (control group) included intact teeth, while the remaining groups included endodontically treated mandibular molars. In group FVC, teeth were restored with full veneer crowns, in group O with onlays, and in group E with endocrowns. All restorations for groups FVC, O, and E were fabricated from lithium disilicate ceramic and bonded using self-adhesive resin cement. A universal testing machine was used for measuring fracture load (in Newtons). The mean fracture load of each group was compared using ANOVA. Results: Mean fracture load and standard deviation for each group were calculated, and Chi-square test and Post Hoc Test, Turkey HSD test, were applied to find statistical significance. The mean fracture load for group C was 755.83±103.17 N, group FVC was 988.09±45.26 N, group O was 902.93±54.45 N, and group E was 972.18±51.78 N, with a significant p-value (< 0.000001) in ANOVA. Further, post hoc analysis gave an insignificant difference in mean fracture load between group FVC and group E. Conclusions: The full veneer crown and endocrown showed the highest fracture resistance with a non-significant difference, whereas natural teeth showed the least fracture resistance. Endocrowns have emerged as a conservative, adhesive indirect restoration option for endodontically treated posterior teeth without involving roots for retention.